Social Development in the Urban Informal Sector: A Case Study of Street Vendors in Pasar Minggu, Jakarta - Nurhayati, Cucu (Masyarakat: Jurnal Sosiologi, 2020)
Street vendors are basically able to sustain the economy of the urban poor. However, their existence is considered to cause disorder in the way they often deal with disciplinary actions organized by the government. The policy set by the provincial government on street vendors should be addressed to the cultural dimension, by minimizing acts of violence and instilling the values of cleanliness and order. Previous studies see street vendors as alternative economic actors who have a stake in the national economy. The studies also put more emphasis on policies (structure) and behaviour of street vendors (culture) so that they do not show sustainable and inclusive development. For this reason, the study in this article adds the dimension of social processes besides discussing the structure and culture under the social development framework in the case of street vendors through interactions that are built between them and the government. It uses surveys as the quantitative method to measure the level or achievements of social development, and applies cluster sampling techniques according to the area and type of commodity. In addition, a qualitative method is also used to explore the meaning of street vendors in dealing with the structure by interviewing and conducting FGDs on market managers, government officials, street vendor associations and street vendors themselves.